Cooperation Policy Implementation Between the Government and Business Entities in the Provision of Infrastructure in Indonesia - Tria Sasangka Putra; Khasan Effendy; Bahrullah Akbar; Sampara Lukman (International Journal of Economics Development Research (IJEDR), 2023)
The problem of not optimal implementation of cooperation policies between the government and business entities in the provision of infrastructure at the Ministry of National Development Planning/National Development Planning Agency of the Republic of Indonesia shows that actually the policy implementation process is still not in accordance with the policy objectives set out in Presidential Regulation Number 38 of 2015, seen from the pattern of implementation, and still has various weaknesses. This study uses a qualitative approach with descriptive methods, namely data collection by interviews, documentation and observation with data analysis, namely data reduction (data reduction), data display (display data), and conclusion drawing/verification (withdrawal of conclusions/verification) with triangulation techniques on the data obtained. The theory used in this study uses the public policy theory of Merilee S. Grindle. Grindle's (1980) model with dimensions: policy content and policy context. The contents of the policy cover (1) interests affected; (2) type of benefits; (3) extent of change envisioned; (4) site of decision making; (5) program implementers; and (6) committed resources. The implementation context includes (1) power, interest, and strategies of the actors involved; (2) institutional and regime characteristics; and (3) compliance and responsiveness. With Grindle's opinion, then the Implementation of PPP Policy in Provision of Infrastructure at the Ministry of National Development Planning/National Development Planning Agency of the Republic of Indonesia will be analyzed according to the content of policy and the context of implementation. The implementation of the Implementation of the Cooperation Policy between the Government and Business Entities in the Provision of Infrastructure at the Ministry of National Development Planning/National Development Planning Agency of the Republic of Indonesia. not yet optimal Researchers create a new model of Government Cooperation Policy with Business Entities in Provision of Infrastructure at the Ministry of National Development Planning/National Development Planning Agency of the Republic of Indonesia Transparency, Regulation, integrated system, Agility (information openness, making laws, digitally integrated system, intelligent leadership).